Confirmatory Factor Analysis of Servant Leadership of Fire and Rescue Officer and Assistants in Bangkok Metropolitan Administration - Therdbhuthadham, Theera; Muakchim, Nathamon (Rajapark Journal, 2021)
This research has the objective to analysis the components of servant leadership of Fire and Rescue Officer and Assistants in Bangkok Metropolitan Administration with the empirical data. There were 310 participants used as a sampling group and were selected by Simple Random Sampling. A questionnaire was used as the research instrument in this study. The Model was validated using confirmatory analysis through AMOS program. The research results indicated that the components of servant leadership were at high and very high levels. The Conceptualization component was the highest score of servant leadership. The model showed its consistency with the empirical data with 2/df = 1.507, P-value = 0.053, GFI= 0.977, CFI = 0.996, RMR = 0.005 and RMSEA = 0.040